2004
DOI: 10.1038/laban0204-26
|View full text |Cite
|
Sign up to set email alerts
|

Virus PCR Assay Panels: An Alternative to the Mouse Antibody Production Test

Abstract: Antibody production tests have traditionally been used to test biological materials for viral contamination. Now molecular biology techniques have emerged as an alternative. The authors compare MAP testing with PCR-based detection methods, focusing on differences in animal use, laboratory requirements, sample size, and limits of detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Frequency of testing will depend on local circumstances. recent reports 25,32 suggest that the incidence of infectious agents in biological materials has markedly decreased over the past decades, but the risk still exists especially for those biologicals that have been stored for a long time and the source of which is ill-documented. For example, outbreaks of ectromelia in the USA caused by contaminated serum 33,34 underline the risk of agent transmission by biological materials.…”
Section: Every 3 Months Annuallymentioning
confidence: 99%
“…Frequency of testing will depend on local circumstances. recent reports 25,32 suggest that the incidence of infectious agents in biological materials has markedly decreased over the past decades, but the risk still exists especially for those biologicals that have been stored for a long time and the source of which is ill-documented. For example, outbreaks of ectromelia in the USA caused by contaminated serum 33,34 underline the risk of agent transmission by biological materials.…”
Section: Every 3 Months Annuallymentioning
confidence: 99%
“…PCR assays appear to be most useful for the identification of parvoviruses in contaminated biomaterials (Bauer et al 2004;Blank et al 2004;Bootz et al 2003), target tissues from infected rodents (e.g., mesenteric lymph node and spleen) (Besselsen 1998;Besselsen et al 1995;Redig and Besselsen 2001;Wan et al 2006), and potentially infected feces and environmental surfaces Kunita et al 2006;Ueno et al 1997).…”
Section: Detectionmentioning
confidence: 99%
“…Recent experiences have shown that even cell-free biologicals have the potential to introduce agents to rodent colonies when imported (Lipman et al, 2000). However, PCR technology has supplanted mouse antibody production/RAP assays and allows direct testing of the materials themselves for the presence of infectious agents (Bauer et al, 2004;Bootz and Sieber, 2002;Blank et al, 2004). However, PCR technology has supplanted mouse antibody production/RAP assays and allows direct testing of the materials themselves for the presence of infectious agents (Bauer et al, 2004;Bootz and Sieber, 2002;Blank et al, 2004).…”
Section: Screening Of Imported Biological Materialsmentioning
confidence: 99%